The Effect of Communication, Leadership and Organizational Culture on Employee Performance: The Case of Population and Civil Registration Office of Palembang City - Irawan, Ferry; Djazuli, Abid; Choiriyah, Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2025)
This study aims to determine 1) the influence of communication, leadership, and organizational culture on employee performance at the Population and Civil Registration Service of Palembang City. 2) The influence of communication on employee performance at the Population and Civil Registration Service of Palembang City. 3) The Influence of Leadership on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 4) The Influence of Organizational Culture on the Performance of Employees of the Population and Civil Registration Service of Palembang City. This type of research is Associative. The variables used by researchers include Communication, Leadership, Organizational Culture, and Performance. The population of this study consisted of all Employees of the Population and Civil Registration Service of Palembang City, and the sample in the study amounted to 101 employees. The sampling technique used was Proportionate Stratified Random Sampling. The data used in this study are primary data collected through a questionnaire. The data analysis technique used is multiple linear regression. The results of this study indicate that: 1) Communication, Leadership, and Organizational Culture have a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 2) Communication has a significant effect on the Performance of Employees of the Population and Civil Registration Service of Palembang City. 3) Leadership has a significant influence on the performance of employees at the Palembang City Population and Civil Registration Service. 4) Organizational culture has a significant influence on the performance of employees at the Palembang City Population and Civil Registration Service.